Poor adherence of randomised trials in surgery to CONSORT guidelines for non-pharmacological treatments (NPT): a cross-sectional study - Nagendran, M; Harding, D; Teo, W; Camm, C; Maruthappu, M; McCulloch, P; Hopewell, S (BMJ Publishing Group, 2013)
OBJECTIVE: To systematically assess adherence of randomised trials in surgery to Consolidated Standards of Reporting Trials (CONSORT) guidelines for non-pharmacological treatments (NPT). Surgical trials are considered more difficult to design and execute than pharmacological trials. Furthermore, the original CONSORT statement does not address some aspects that are vital to the transparent reporting of surgical trials. The CONSORT-NPT extension was designed to address these issues but adherence in medical and surgical journals has not been assessed. DESIGN: Cross-sectional study. SAMPLE: We identified eight general medical and eight surgical journals, indexed in PubMed and published in 2011, with the highest impact factors in their respective categories. MAIN OUTCOMES: Adherence to CONSORT statement and CONSORT-NPT extension items. RESULTS: We identified 54 surgical trials (22 published in medical journals and 32 in surgical journals). There were eight items for which there was less than 30% overall compliance (seven were specific to the CONSORT-NPT extension). These seven items are related to: a full description of the care providers, centres and blinding status in the abstract (n=7/54, 13%), eligibility criteria for centres performing the interventions (n=13/54, 24%), how adherence of care providers with the protocol was assessed or enhanced (n=7/54, 13%), how clustering by care providers or centres was addressed as it relates to sample size (n=3/54, 6%), how care providers were allocated to each group (n=9/54, 17%), how clustering by care providers or centres was addressed as it relates to statistical methods (n=2/54, 4%), a description of care providers (case volume, qualification, expertise, etc) and centres (volume) in each group (n=0/54, 0%). CONCLUSIONS: Adherence of surgical trials to CONSORT-NPT extension items is much poorer than to the standard CONSORT statement. Adherence also appears to be superior in general medical journals compared with surgical journals. Raising awareness and conducting qualitative research to identify areas for specific intervention will be important going forward.